Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1600 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Prosopis africana (Guill. & Perr.) Taub.", "Geometry POLYGON((-180 -82,-180 82,180 82,180 -82,-180 -82))", "HasGeospatialIssue is false" ] } The dataset includes 1600 records from 21 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001114-150504100648427/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences